The Limitations of Navigating ChatGPT as Writing Assistance Tools in EFL Writing Activities - Vivi Aulia; Yamin, Moh. (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
The process of learning languages has experienced and improved rapidly as a result of the advancement of artificial intelligence (AI) technologies. A specific area that has shown the improvement is the integration of this AI in EFL learning. The purpose of this systematic review is to investigate and to explore current research on the limitations of using ChatGPT as a writing assistance tool for EFL writing activities from different nations in the world. The PRISMA 2020 checklist was employed in this research. DOAJ, ERIC, and Google Scholar as international article databases were used to select research articles being analyzed. Fifteen articles that met the inclusion criteria were selected. The analysis of these articles showed that ChatGPT has three main limitations in writing area. First, 7 of 15 articles report that it cannot fully assist students throughout the writing process. Secondly, 10 of 15 articles present an issue concerning over-reliance and writing originality. Finally, 4 of 15 articles mention that the feedback given by ChatGPT is inaccurate in some cases. This research concludes that EFL teachers should accompany and assist their students in using technology for writing activities. Its application should be advisable, wise, and considering the specific writing context